Tahapan dan Karakter Perkembangan Belajar Siswa SD - Ani Budiarti Tohari; Murfiah Dewi Wulandari; Darsinah Darsinah (Peneliti.net, 2022)
Abstract Teaching and learning activities at the elementary school level are not the same or different from teaching and learning activities at other levels of education, because teaching and learning activities at the elementary school level pay attention to various aspects, including physical, cognitive and psychosocial. This results in the process of teaching and learning activities being less suited to these characters, thus teaching and learning activities that are not appropriate will result in the quality of teaching and learning activities being developed less than optimal, therefore it is necessary to study the best possible character of elementary school development. With the three aspects of development, both physical, cognitive and psychosocial, there will be a need that forms the basis for elementary school teachers in developing quality teaching and learning activities. Keywords: Stages, Character, Teaching and Learning ActivitiesAbstrakKegiatan belajar mengajar ditingkat sekolah dasar tidak sama atau berbeda dengan kegiatan belajar mengajar pada jenjang pendidikan lainya, karena kegiatan belajar mengajar tingkat sekolah dasar memperhatikan berbagai aspek antara lain fisi, kognitif dan psikososial. Hal ini berakibat proses kegiatan belajar mengajar menjadi kurang pas dengan karakter tersebut, dengan demikian kegiatan belajar mengajar yang tidak sesuai tersebut maka kualitas kegiatan belajar mengajar yang dikembang akan kurang maksimal, oleh karena itu perlu dikaji yang sebiak-baiknya karakter perkembangan sekolah dasar. Dengan ketiga aspek pengembangan itu baik fisi, kognitif dan psikososial maka akan tercipta kebutuhan yang menjadi dasar bagi guru sekolah dasar dalam pengembangan kegiatan belajar mengajar yang berkualitas.